(untitled) (Research, Society and Development, 2022)
Objective: To identify the factors that trigger stress in nursing professionals who worked on the front lines in the fight against COVID-19. Method: This is a descriptive, cross-sectional study with a qualitative approach, carried out at a University Hospital in the Northeast of Brazil. 66 nursing professionals who worked in the COVID-19 sector participated in the study. Data were analyzed using simple descriptive statistics and concepts were analyzed by lexicographical analysis supported by the IRAMUTEQ software. Results: it was possible to identify that the stressors were divided into two types: 1) Individual factors: fears and apprehensions regarding the care given to the patient; 2) Structural factors in the health service. Conclusion: the main stressors described by the nursing professionals were their feelings of fear of the unknown and the disease, as well as situations in the work environment such as constant losses and the possibility of contamination.